SOA-Based IT Infrastructure Planning Strategy to Optimize Network Management in Companies - Putri, Nanda Aulia; Umami, Nila Niswatun; Sulistiani, Heni; Amelia, Siska (IC-ITECHS, 2024)
This research aims to develop a Service Oriented Architecture (SOA)-based information technology (IT) infrastructure planning strategy to optimize network management in the company. In the increasingly complex digital context, companies require flexible and integrated IT infrastructure to enhance operational efficiency. The methodology used includes stakeholder needs analysis and mapping of network management functions based on the FCAPS reference. (Fault, Configuration, Accounting, Performance, Security). Through interviews and observations of the current infrastructure conditions, this research found that the implementation of SOA can enhance interoperability between applications and simplify the management of IT resources. The resulting design includes logical and physical topologies aimed at improving the reliability and security of the network management system. It is expected that the implementation of this strategy will enhance service performance and provide added value to the company in facing dynamic business challenges.